1993
DOI: 10.1177/096368979300200206
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli Cell-Enriched Fractions in Successful Islet Cell Transplantation

Abstract: Prolonged survival of Islet- allo- and xenografts can be induced following implantation of the islets into the abdominal testis of diabetic rats. We previously showed that a factor released by Sertoli cells appears to be responsible for the protection of the intratesticular islet allo- and xenografts against rejection. The aim of this study was to examine whether an immunologically privileged site can be established in an organ site in vivo, other than the testis, such as the renal, subcapsular space, to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(83 citation statements)
references
References 27 publications
3
78
0
1
Order By: Relevance
“…These two biological factors must have increased accessibility of injected virus particles to Sertoli cells in the seminiferous tubules and may have allowed us to use low virus titers (1 to 20 ϫ 10 5 pfu͞ml) in inducing Sertoli cell infection without triggering inflammation, as observed in the previous study using significantly higher virus titer (3 ϫ 10 12 pfu͞ml) (18). Although much remains to be investigated about the level of immune privilege in the testis, studies have shown that even dissociated Sertoli cells have ability to suppress rejection after transplantation (33,34), and this local immunosuppresion by Sertoli cells must have contributed to the absence of inflammatory reaction. Other factors also may be involved, but the unique microenvironment in the infertile testis may account for the long-term transgene expression in Sertoli cells seen in this study.…”
Section: Discussionmentioning
confidence: 90%
“…These two biological factors must have increased accessibility of injected virus particles to Sertoli cells in the seminiferous tubules and may have allowed us to use low virus titers (1 to 20 ϫ 10 5 pfu͞ml) in inducing Sertoli cell infection without triggering inflammation, as observed in the previous study using significantly higher virus titer (3 ϫ 10 12 pfu͞ml) (18). Although much remains to be investigated about the level of immune privilege in the testis, studies have shown that even dissociated Sertoli cells have ability to suppress rejection after transplantation (33,34), and this local immunosuppresion by Sertoli cells must have contributed to the absence of inflammatory reaction. Other factors also may be involved, but the unique microenvironment in the infertile testis may account for the long-term transgene expression in Sertoli cells seen in this study.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4] This immunoprotective environment is due in part to the secretion of immunosuppressive molecules by Sertoli cells (SCs) [5][6][7] that allow ectopically transplanted SCs to survive as allografts [8][9][10] and concordant (rat-to-mouse) 11 and discordant (pig-to-rat) 12,13 xenografts in rodents. In addition to the ability of transplanted SCs to protect themselves in immunologically foreign environments, SCs were shown to protect islets and neuronal cells from immunemediated rejection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ability of transplanted SCs to protect themselves in immunologically foreign environments, SCs were shown to protect islets and neuronal cells from immunemediated rejection. 9,10,[14][15][16][17][18][19] The ability of SCs to protect themselves from immunemediated destruction, as well as their ability to produce a variety of proteins, has novel and potentially far-reaching implications for gene therapy. Gene therapy is an emerging field with the goal of replacing defective and deficient proteins to restore function in disease states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in humans a similar disease with a dysfunction of CD95 was reported [43Ϫ45]. Children with autoimmune lym-layed rejection when co-implanted with CD95L-expressing testis tissue [63]. phoproliferative syndrome (ALPS), also called Canale-Smith syndrome, have massive nonmalignant lymphadenopathy, hepa-CD95L-mediated depletion of cytotoxic T-lymphocytes may not only be beneficial but may also play a role for tumor cells tosplenomegaly, altered T cell populations and other manifestations of systemic autoimmunity.…”
mentioning
confidence: 99%